Measurement of the W+W?W+W? cross section in pp collisions at s?=8s=8 TeVand limits on anomalous gauge couplings - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
A measurement of the W boson pair production cross section in proton-proton collisions at ?s = 8 TeV is presented. The data collected with the CMS detector at the LHC correspond to an integrated luminosity of 19.4fb-1. The W +W - candidates are selected from events with two charged leptons, electrons or muons, and large missing transverse energy. The measured W +W - cross section is 60.1 ± 0.9 (stat) ± 3.2 (exp) ± 3.1 (theo) ± 1.6 (lumi) pb = 60.1±4.8 pb, consistent with the standard model prediction. The W +W - cross sections are also measured in two different fiducial phase space regions. The normalized differential cross section is measured as a function of kinematic variables of the final-state charged leptons and compared with several perturbative QCD predictions. Limits on anomalous gauge couplings associated with dimension-six operators are also given in the framework of an effective field theory. The corresponding 95 % confidence level intervals are -5.7<cWWW/?2<5.9TeV-2, -11.4<cW/?2<5.4TeV-2, -29.2<cB/?2<23.9TeV-2, in the HISZ basis. © 2016, CERN for the benefit of the CMS collaboration.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Measurement of the W +W - cross section in pp collisions at ?s= 8 TeVand limits on anomalous gauge couplings. European Physical Journal C, 76(7). doi:10.1140/epjc/s10052-016-4219-1